Recent advances in mechanism and anticoagulant therapy of venous thromboembolism in patients with non-dialysis chronic kidney disease - Jia-xin Wang; Yang-bin Pan (Editorial Department of Journal of Clinical Nephrology, 2024)
Chronic kidney disease （CKD） patients are at an elevated risk of thromboembolism, cerebral infarction and myocardial infarction. The incidence of fatal thrombotic complications has been rising over the years. It may be attributed to uremic toxin accumulation, blood coagulation dysfunction, platelet activation and abnormal hemostasis associated with CKD. Therefore dose adjustments and drug selections for antiplatelet and anticoagulant therapy should be based upon the level of glomerular filtration rate （GFR）. This review summarized the underlying mechanisms of thromboembolic complications and recent advances of anticoagulant therapy for non-dialysis CKD patients.